Study of the Electronic delocalization in Silicon organic derivatives of benzene and their corresponding anion radicals (2006)
The silicon organic compounds phenyltrimethylsilane (1), 1,4-bis(trimethylsilyl)benzene (2), diphenyldimethylsilane (3) y 1,1,2,2-dibenzobis(dimethyls ilane) (4) were synthesized and characterized by IR, NMR-1 H and elemental analysis. They were also reduced to the corresponding silicon radical anions: Potassium trimethylsilylphenylide (1a), Potassium 1,4-bis(trimet hylsilylphenylide (2a), Potassium dimethylsilyl-diphenylide (3a), Potassium 1,1,2,2-bis(di methylsilylphenylide) (4a). The electronic delocalization study was made by UV spectroscopy and complex impedance. By UV spectroscopy evidence was found a bathochromic shift in the following order: silicon radical anions, organosilicon and the analogous carbonate precursors, which is consistent with the electronic delocalization. By impedance spectroscopy, information about the type of impedance and the magnitude of the dc conductivity for the carbonates and silicon com compounds, as well as their silicon radical anions were obtained. These results allowed us to identify the silicon derivatives of benzene and their corresponding reduced compounds in the range of the semiconductors and those of the analogous carbonates in the non conducting materials